Visible-light-driven melamine foam/PANI/N, O, P containing covalent organic polymer for achieving H2O2 production and boosting Fe(Ⅱ)/Fe(Ⅲ) cycle. (15th April 2022) - Lin, Aijun; Ren, Meng; Tan, Xiao; Ma, Jun; Zhang, Yu; Yang, Tianxue; Pei, Yuansheng; Cui, Jun
Abstract: Low transparency of the wastewater as one of the limitations weakens photocatalyst activity. Herein, a self-floating melamine foam/polyaniline (PANI)/N, O, P-containing covalent organic polymer (MF/PANI/NOP–COP) photocatalyst was successfully synthesized to achieve in-situ H2 O2 production and boost Fe(Ⅱ)/Fe(Ⅲ) cycle, exhibiting a strong catalytic activity for treating high chroma wastewater. Compared with the PANI/NOP–COP powder, the Rhodamine B degradation and mineralization efficiencies were enhanced by 3.5 and 6.6 times in the presence of the self-floating MF/PANI/NOP–COP, respectively. The enhanced catalytic activity was derived from the satisfied visible light harvest performance (4.8%) and the high surface charge injection efficiency (96.4%) in the high chroma environment. Meanwhile, 179 ± 29.5 μM H2 O2 was generated and the stabilized Fe(Ⅱ) concentration was increased from 0.21 mM to 0.45 mM, reducing the additive dosages of Fe(Ⅱ) and H2 O2 . Moreover, the self-floating MF/PANI/NOP–COP exhibited an easy-to-recycle property and a broadened range of pH application (2–6). The high-efficiency degradation performance was owing to the sustainable generation of OH at the Fenton/photocatalysis dual reaction activity centres in the photocatalysis-self-Fenton system. Graphical abstract: Image 1 Highlights: A self-floating MF/PANI/NOP–COP photocatalyst is synthesized for treating high chroma wastewater. The H2 O2 production and Fe(Ⅱ)/Fe(Ⅲ) cycle processes are boosted by MF/PANI/NOP–COP. Dual reaction activity centres are constructed to maintain good degradation performances.